Trypanosomatid cysteine protease activity may be enhanced by a kininogen-like moiety from host serum - Lonsdale-Eccles, John D.; Mpimbaza, G.W.N.; Nkhungulu, Z.R.M.; Olobo, J.; Grab, D.J. (1995)
African trypanosomes contain cysteine proteases (ttypanopains) the activity of which can be measured by in vitro digestion of fibrinogen, after electophoresis in fibrinogen-containing SDS/polyacrylamide gels. When assessed by this procedure, trypanopain from Trypanosoma brucei (trypanopain-Tb) is estimated to have a molecular mass of 28 kDa. However, two additional bands of trypanopain activity (87 kDa and 105 kDa) are observed if serum is added to the trypanopain before electrophoresis. Formation of the 87 and 105 kDa bands is frequently accompained by a reduction in the intensity of the 28 kDa activity which suggests that the extra bands are complexes of the 28 kDa trypanopain-Tb and a molecule from rat serum called rat trypanopain moledulator (rTM). The rTM-induced activation of cysteine proteases is not restricted to T. brucei as it is also observed with proteases from other protozoan parasites such as bloodstream forms of Trypanosoma congolense and the mammalian-infective in vitro-derived promastigote forms of Leishmania donovani and Leishmania major. The physical properties of rTM resemble those of the kininogen family of cysteine protease inhibitors. rTM is an acidic (pI 4.7) heat-stable 68 kDa blycoprotein with 15 kDa protease-susceptible domains. This resemblance between rTM and kininogens was confirmed by the positive, albeit weak, immunoreacitivity between anti (human low-molecular-mass kininogen) antibody and rTM as well as anti-rTM antibody and human low-molecular-mass kininogen. Furthermore, commercial preparations of human-low-molecular-mass kininogen and chicken egg white cystain mimicked rTM by forming extra bands of proteolytic activity in the presence of trypanopain-Tb. In some instances, low-molecular-mass kininogen was also observed to increase the rate of hydroloysis of 7-(benzyloxycarbonyl-phenylalanyl-arginylamido)-4-methylcoumarin by live T. brucei. Although this effect was rather erratic, in no instance was significant inhibition observed when this putative cysteine protease inhibitor was used under these conditions. The activation of parasite cysteine proteases by commonly accepted cysteine protease inhibitors is unexpected and may have important pathological repercussions.